Cinical Medicine - Paramasivan, P., 1985-; Rajest, S. Suman, 1988-; Chinnusamy, Karthikeyan, 1973-; R, Regin, 1985-; Joseph, Ferdin Joe John, 1987- (Hershey, PA : IGI Global, 2024)
"The book delves into the realm of Explainable AI to explore novel methodologies for analyzing human behavior in natural settings. By focusing on facial expressions, gestures, and body movements, this book presents cutting-edge research, databases, benchmarks, algorithms, and systems in the domain of machine analysis of human behavior"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Artificial intelligence -- Medical applications; Clinical medicine -- Data processing